ORGANIZATION OF SELF-STUDY OF STUDENTS IN THE HIGHER EDUCATION SYSTEM USING DIGITAL TECHNOLOGIES - Jurayeva Nargiza Oltinboyevna (Western European Studies, 2024)
In this article, there is a brief description of the use of mobile software applications in the organization of students' independent education and the ways to increase the efficiency of students' independent education and the ways to increase students' self-confidence and interest in science with the help of mobile software applications; data is provided
Keywords: independent education; mobile application; mobile education